Design and rationale of the EBBINGHAUS trial: A phase 3, double‐blind, placebo‐controlled, multicenter study to assess the effect of evolocumab on cognitive function in patients with clinically evident cardiovascular disease and receiving statin background lipid‐lowering therapy—A cognitive study of patients enrolled in the FOURIER trial. Issue 2 (16th February 2017) - Giugliano, Robert P.; Mach, Francois; Zavitz, Kenton; Kurtz, Christopher; Schneider, Jingjing; Wang, Huei; Keech, Anthony; Pedersen, Terje R.; Sabatine, Marc S.; Sever, Peter S.; Honarpour, Narimon; Wasserman, Scott M.; et al.
Abstract : Some observational studies raised concern that statins may cause memory impairment, leading to a US Food and Drug Administration warning. Similar questions were raised regarding proprotein convertase subtilisin/kexin‐type 9 inhibitors (PCSK9i) and neurocognitive function. No prospectively designed study has evaluated the relationship between long‐term PCSK9i use and cognition changes. Patients with prior cardiovascular disease treated with maximally tolerated statin enrolled in FOURIER (the randomized, double‐blind, placebo‐controlled cardiovascular outcome study of the PCSK9i evolocumab) could participate in this prospective assessment of cognitive function (EBBINGHAUS). Key additional exclusion criteria for EBBINGHAUS were dementia, cognitive impairment, or other significant mental or neurological disorder. Cognitive testing was performed using the Cambridge Neuropsychological Test Automated Battery, a tablet‐based tool assessing executive function, working memory, memory function, and psychomotor speed at baseline, weeks 24 and 48, every 48 weeks thereafter, and study end. The primary endpoint was spatial working memory strategy index of executive function (SWMSI). The primary hypothesis was that evolocumab would be noninferior to placebo in the mean change from baseline over time in SWMSI. Fifteen hundred cognitively normal patients completing the assessments provided approximately 97% power to demonstrate that the upper 95% confidence interval for the treatment difference in mean change from baseline in SWMSI over time is <20% of the SD of the mean change in the placebo group. An exploratory analysis will compare neurocognitive function in patients with post‐baseline low‐density lipoprotein cholesterol <25 mg/dL. EBBINGHAUS will evaluate whether the addition of evolocumab to statin therapy affects cognitive function over time in patients with stable cardiovascular disease.